The development of the meaning of non-ostensive words in a group of primary school children - Segal, Denise Erica (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1986)
The purpose of the present study was to investigate word meaning and its development in primary school children (6-12 years) . It was argued that the learning and development of the meanings of words such as pain cannot be primarily explained by means of ostensive definition. Furthermore, existing theories of word meaning which deal predominantly with substantive words fail to account for the learning of non-ostensive words. The pertinent psychological, linguistic and developmental psycholinguistic approaches to word meaning are reviewed briefly. The prototype approaches to word meaning are modified to apply to non-ostensive words . The focus is on conceptual meaning, that is, the way in which the senses of a word alter in different contexts. It is argued that the meaning of the word is its use in a diversity of linguistic contexts. The term "grammar" is applied in a unique way to encompass the meaning of the word (which stems in part from the words with which it co-occurs) as well as its selective use with other words in the language. Ninety-five metalinguistically-phrased tasks comprising short questions and picture-story sequences were analyzed in depth. The tasks were administered individually. A flexible interview afforded additional probing for each question. The analysis comprised percentage scores of responses at different age levels together with verbatim transcripts and qualitative descriptions: Uniformity, variation and developmental trends were found on different tasks for any particular word. Developmental trends were noted in children's understanding of particular words (for example, same), thereby extending the findings of previous researchers. There was evidence for a progression in children's ability to take into consideration that a word alters its sense according to the linguistic context in which it occurs (for example, same as it relates to chair versus dress versus pain). A comprehensive account of the words meaning could be established when a diversity of tasks was applied for each word. Children of different age levels employed different strategies in answering the questions posed. A model is proposed to describe the development of the meaning of non-ostensive words during the primary school years. It is suggested that psycholinguistic studies on word meaning be re-evaluated and that language and reading programmes incorporate the notion of "grammar". Application of this approach to the study of substantive word meaning in preschool children has important implications for theories of word meaning and for therapeutic intervention.
Keywords: Connotation (Linguistics); Children -- Language; Language acquisition